The Social Life of Financial Derivatives : Markets, Risk, and Time - LiPuma, Edward, 1951- (Book collections on Project MUSE., 2017)
Drawing on ethnographic fieldwork and his experience trading derivatives, Edward LiPuma theorizes the profound social dimensions of derivatives markets and the processes, rituals, mentalities, and belief systems that drive them.